A dream of waters glittering with stars (Análisis de la Realidad Nacional, 2025)
Revista Análisis de la Realidad Nacional publishes what is perhaps the only text that Miguel ÁngelAsturias wrote in English, entitled Â«A dream of shining waters with starsÂ». The United Nations Educational,Scientific and Cultural Organization included it in the book entitled Impact of science on society,published in France in 1969.